The Adsorption Mechanism of Activated Carbon and Its Application - A Review - Muhammad S. Muzarpar; A. M. Leman; Norhafsam Maghpor; Nik Normunirah Mat Hassan; Norasyikin Misdana (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2020)
Activated carbon (AC) was recognized by many researchers as useful substance in adsorption of impurities. Several processes involved in the production of AC which were carbonization, crushing, and activation process. Carbonization of carbon required high temperature up to 900oC. Then the carbon will be crush to a desired size for activation process. Activation of carbon can be either chemical activation, physical activation or combination of chemical and physical activation which called physiochemical activation. The mechanism adsorption of AC commonly due to its micropore present in the carbon or the weak vander waals forces which can attract the impurities. Activated carbon have multiple function in human daily life. This study will be discuss the function of AC in the production face mask, water filtration and air filtration.